Quick Response Codes in Busy Books: A Strategy to Engage in Geometry Learning for Elementary Students - Zaid Zainal; Eva Salviana J.; Wawan Krismanto (Universitas Pendidikan Ganesha, 2026)
Learning engagement is a crucial factor in elementary mathematics education as it contributes to students' motivation, active participation, and learning achievement. However, geometry instruction is still predominantly supported by conventional learning media that have not been able to provide interactive and meaningful learning experiences. This study aims to analyze the needs and develop a QR Code-integrated busy book as a mathematics learning medium to facilitate students' learning engagement in three-dimensional geometry. The study employed a Research and Development (R&D) approach using the ADDIE model, involving 78 elementary school students, three teachers, and three expert validators. Data were collected through observations, interviews, needs analysis questionnaires, validation sheets, and practicality questionnaires, and were analyzed using qualitative and quantitative descriptive techniques. The findings indicate that both teachers and students require more interactive learning media to enhance learning engagement in geometry instruction. The developed product is a QR Code-integrated busy book that combines hands-on learning activities with access to digital learning materials. The validation results confirmed that the learning media met the required validity criteria, while the practicality test demonstrated that it was easy for both teachers and students to use. This study concludes that the QR Code-integrated busy book is a valid and practical learning medium for promoting students' learning engagement. The findings imply that integrating interactive printed media with digital technology offers an innovative alternative for creating mathematics learning environments that are more active, engaging, and student-centered.